2018
DOI: 10.1002/pssb.201800370
|View full text |Cite
|
Sign up to set email alerts
|

The Formation and Evolution of Defects in Nanocrystalline Fe During Indentation: The Role of Twins in Pop‐Ins

Abstract: Nanoindentation is a most common experimental tool used for obtaining information on the mechanical behavior of materials. This is done by qualitatively relating the occurrence of pop‐ins (in the load–displacement plots) to microstructural changes such as dislocation formation, fracture of surface oxides, or slip transmission. The present study takes a first approach in directly verifying the micro‐plasticity processes that give rise to such pop‐ins by performing molecular dynamics indentation simulations in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The interaction of twins and dislocations with grain boundaries results in pop‐in effects. [ 53 ] Dislocations’ annihilation or splitting, twins’ migration or growth, and de‐twining of the preexisting twins could also cause the pop‐ins. [ 53 ] The pop‐in phenomenon has been reported in various deformed alloys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of twins and dislocations with grain boundaries results in pop‐in effects. [ 53 ] Dislocations’ annihilation or splitting, twins’ migration or growth, and de‐twining of the preexisting twins could also cause the pop‐ins. [ 53 ] The pop‐in phenomenon has been reported in various deformed alloys.…”
Section: Resultsmentioning
confidence: 99%
“…[ 53 ] Dislocations’ annihilation or splitting, twins’ migration or growth, and de‐twining of the preexisting twins could also cause the pop‐ins. [ 53 ] The pop‐in phenomenon has been reported in various deformed alloys. For instance, Hu et al [ 11 ] reported pop‐in events in the ultrafine‐grained AZ31 magnesium alloy.…”
Section: Resultsmentioning
confidence: 99%
“…The other twin and crack formation mechanisms are discussed in the transition from pure elastic to other behaviors. Twin formation upon plasticity initiation has been reported in sapphire [78], high-Mn steel [79], Ta [80], Mg-6Zn [81], and nanocrystalline (nc)-Fe [82]. Crack initiation can also be the dominant mechanism for the event, as shown mainly in brittle materials, including polycrystalline alumina [83], TiN-based thin-film coatings [84,85], Si and Ge [86,87], tungsten carbide [88], and various ceramics [89].…”
Section: Experimental Clarificationmentioning
confidence: 99%
“…Kuhr and K.E. Aifantis took a first approach in directly verifying the micro‐plasticity processes that give rise to pop‐ins in the load‐displacement plots by performing molecular dynamics indentation simulations in bcc Fe‐nanocrystals with a Σ5 symmetric tilt boundary. T. Radchenko et al combined two theoretical approaches, grazing dynamical diffraction and efficient numerical simulations, for studying electronic properties in uniaxially strained graphene layers with impurity atoms.…”
mentioning
confidence: 99%